2020
DOI: 10.1111/nph.16624
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the sharing of foliar fungal pathogens by the invasive plant Ageratina adenophora and its neighbours

Abstract: Summary Local pathogens can accumulate as asymptomatic endophytes, making it difficult to detect the impacts of invasive species as propagators of disease in the invaded range. We used the invasive plant Ageratina adenophora to assess such accumulation. We intensively collected foliar fungal endophytes and leaf spot pathogens of A. adenophora and co‐occurring neighbours and performed an inoculation experiment to evaluate their pathogenicity and host range. Ageratina adenophora harboured diverse necrotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 69 publications
4
33
0
Order By: Relevance
“…Further experiments indicated that 25.3% of foliar pathogens were seedborne ( Fig. 2a, Raw data), including one dominant pathogen, OTU1 (Allophoma cylindrispora, family Didymellaceae; an unidentified OTU515 was observed in our previous report (Chen et al 2020b)), accounting for 15.6% of total foliar pathogens (Raw data).…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Further experiments indicated that 25.3% of foliar pathogens were seedborne ( Fig. 2a, Raw data), including one dominant pathogen, OTU1 (Allophoma cylindrispora, family Didymellaceae; an unidentified OTU515 was observed in our previous report (Chen et al 2020b)), accounting for 15.6% of total foliar pathogens (Raw data).…”
Section: Discussionmentioning
confidence: 55%
“…We focused our multiple infections at the leaf spot level, rather than the host individual level, because (i) a multiple infection within-leaf spot should include both direct and indirect interactions of pathogens (Tollenaere et al 2016) and (ii) multiple fungal species or genotypes from one species have been observed to co-occur in the same spots of Eucalyptus (Crous et al 2009, Perez et al 2010; thus, multiple infections in one leaf spot should be common but remain to be characterized. Previously, we reported the foliar pathogen sharing of A. adenophora with local plants in Yunnan Province, which is a relatively old invasion area (Chen et al 2020b). In this case, we expanded the sampling areas into two newly established neighbouring provinces, Guizhou and Guangxi.…”
Section: Study Sites and Sample Collectionsmentioning
confidence: 99%
See 3 more Smart Citations